Place making as a form of place taking: Residential displacement and grassroots resistance to institutional encroachment in Buffalo, New York. Issue 4 (6th August 2019) - Silverman, Robert Mark; Taylor Jr, Henry Louis; Yin, Li; Miller, Camden; Buggs, Pascal
Abstract : Purpose: The purpose of this paper is to examine perceptions of institutional encroachment and community responses to it. Specifically, it focuses on residents' perceived effects of hospital and university expansion and the role of place making on gentrification in core city neighborhoods. This study offers insights into the processes driving neighborhood displacement and the prospects for grassroots efforts to curb it. Design/methodology/approach: Data were collected through focus groups with residents and other stakeholders in working class, minority neighborhoods which were identified as being in the early stages of gentrification. Nine focus groups were held across three neighborhoods experiencing institutional encroachment. The analysis was guided by standpoint theory, which focuses on amplifying the voices of groups traditionally disenfranchized from urban planning and policy processes. Findings: The findings suggest that residents perceived institutional encroachment as relatively unabated and unresponsive to grassroots concerns. This led to heightened concerns about residential displacement and concomitant changes in the neighborhoods' built and social environments. Experiences with encroachment also increased residents' calls for greater grassroots control of development. Originality/value: This analysis illuminates how gentrification and displacement results from both physical redevelopment activities of anchor institutions and their decisions related to place making. The conclusions highlight the importance of empowering disenfranchized groups in the place-making process to minimize negative externalities at the neighborhood level.